EP300‐related Rubinstein–Taybi syndrome: Highlighted rare phenotypic findings and a genotype–phenotype meta‐analysis of 74 patients. Issue 12 (11th October 2020) - Cohen, Jennifer L.; Schrier Vergano, Samantha A.; Mazzola, Sarah; Strong, Alanna; Keena, Beth; McDougall, Carey; Ritter, Alyssa; Li, Dong; Bedoukian, Emma C.; Burke, Leah W.; Hoffman, Amber; Zurcher, Victoria; et al.
Abstract: Pathogenic variants in the homologous and highly conserved genes— CREBBP and EP300— are causal for Rubinstein–Taybi syndrome (RSTS). CREBBP and EP300 encode histone acetyltransferases (HAT) that act as transcriptional co‐activators, and their haploinsufficiency causes the pathology characteristic of RSTS by interfering with global transcriptional regulation. Though generally a well‐characterized syndrome, there is a clear phenotypic spectrum; rare associations have emerged with increasing diagnosis that is critical for comprehensive understanding of this rare syndrome. We present 12 unreported patients with RSTS found to have EP300 variants discovered through gene sequencing and chromosomal microarray. Our cohort highlights rare phenotypic features associated with EP300 variants, including imperforate anus, retained fetal finger pads, and spina bifida occulta. Our findings support the previously noted prevalence of pregnancy‐related hypertension/preeclampsia seen with this disease. We additionally performed a meta‐analysis on our newly reported 12 patients and 62 of the 90 previously reported patients. We demonstrated no statistically significant correlation between phenotype severity (within the domains of intellectual disability and major organ involvement, as defined in our Methods section) and variant location and type; this is in contrast to the conclusions of some smaller studies and highlights the importance of large patient cohorts in characterization of this rare disease.